Determinación de la calidad y fragilidad visual de los componentes de las unidades del paisaje del páramo el Chivo, en la parroquia Angamarca provincia de Cotopaxi propuesta de conservación, 2023 - Acurio Garay, Eduardo Mauricio (2023)
The present research project focuses on the landscape assessment of the “El Chivo” moor, located in the Angamarca Parish of the Pujilí Canton, whose main objective is to analyze the quality of the landscape using methodologies such as; the visual quality analysis method Resource Management (VRM) and the Visual Absorption Capacity (CAV) method, these methodologies consider aspects such as texture, color, relief and vegetation to evaluate the different units of the landscape, their purpose is to generate an analysis of the quality and visual fragility of the components of the moor and develop a conservation proposal, and thus be able to generate an analysis of the quality and visual fragility of the components of the moor units and develop a conservation proposal for it, to carry out In this research, field visits were carried out in order to obtain a close knowledge of the activities that take place in the area. By applying the VRM method, a result was obtained that indicates an average quality of the landscape, with a value of 18.5. On the other hand, the CAV method revealed a medium fragility of the landscape, with a weighting of 25.5, thanks to this methodological application the landscape exhibits a medium fragility, with areas that have a moderate regeneration potential, to preserve the valuable natural resources present. in the “El Chivo” moor and guarantee favorable environmental conditions, it is recommended to implement management measures that protect and conserve the natural landscape.